Penerapan Bioteknologi Dalam Produksi Ternak Untuk Meningkatkan Produk Asal Hewan - Muchlis, Ahmad; Sema, Sema; Toleng, Abdul Latief; Sonjaya, Herry (Jurnal Ilmu dan Teknologi Peternakan Terpadu, 2022)
Biotechnology is a field that utilizes biological processes of organisms to generate products that are useful to humans. Furthermore, the relatively high cost of biotechnology and the general lack of knowledge among farmers are reasons why this method must be developed to be more economical and easier to use. The review article aims to review the successful applications of biotechnology in the field of farming that have been implemented, showing the increase in population production, genetic quality, and improvement of livestock animals.